Identification of iron metabolism-related genes in the circulation and myocardium of patients with sepsis via applied bioinformatics analysis - Zhang, Renlingzi; Di, Chong; Gao, Hanlu; Zhu, Yunlou; Li, Congye; Zhu, Zhengfang; Wang, Qixing; Wang, Junjie; Zhou, Feng; Wang, Sheng (Frontiers in Cardiovascular Medicine, 2023)
Background: Iron metabolism plays a vital role in the pathogenesis of sepsis, and potential iron metabolism-related genes involved in sepsis-induced cardiomyopathy remain unknown. This study was designed to explore the key iron metabolism-related genes (IMRGs) involved in circulatory and myocardial pathology in patients with sepsis. Methods: A bioinformatics analysis was conducted to identify IMRGs differentially expressed in the myocardium and peripheral blood mononuclear cells (PBMCs) of patients with sepsis. To identify hub genes, we used Cytoscape to construct a protein–protein interaction network. Immune infiltration of the septic myocardium was assessed using single-sample gene set enrichment analysis (ssGSEA). Cox regression was performed using a multivariate analysis model with potential IMRGs, the patient’s risk score was calculated according to the model, and the correlation between risk score and survival outcome was determined. We also verified the expression of key mRNAs in the myocardium of mice with sepsis using quantitative PCR (qPCR) analysis. Results: Common potential IMRGs were identified in PBMCs and myocardium, among which HIF1A, HMOX1, GLRX5, ABCC5, and NCOA4 might be potential therapeutic targets and predict the prognosis in septic cardiomyopathy.